2015
DOI: 10.1111/jcmm.12725
|View full text |Cite
|
Sign up to set email alerts
|

iPSC‐derived human cardiac progenitor cells improve ventricular remodelling via angiogenesis and interstitial networking of infarcted myocardium

Abstract: We investigate the effects of myocardial transplantation of human induced pluripotent stem cell (iPSC)‐derived progenitors and cardiomyocytes into acutely infarcted myocardium in severe combined immune deficiency mice. A total of 2 × 105 progenitors, cardiomyocytes or cell‐free saline were injected into peri‐infarcted anterior free wall. Sham‐operated animals received no injection. Myocardial function was assessed at 2‐week and 4‐week post‐infarction by using echocardiography and pressure‐volume catheterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Role of telocytes in the heart in health and diseases [Liskova et al, 2017] Arkh Patol c-kit Myocardial telocytes: a specific new cellular entity [Kostin, 2010] Telocytes form networks in normal cardiac tissues The failing human heart is characterized by decreased numbers of telocytes as result of apoptosis and altered extracellular matrix composition [Richter and Kostin, 2015] iPSC-derived human cardiac progenitor cells improve ventricular remodeling via angiogenesis and interstitial networking of infarcted myocardium [Ja et al, 2016] Cardiac telocytes as principal interstitial cells for myocardial reparation and regeneration after infarction -our hope [Varga et al, 2017a] Bratisl Lek Listy J Cell Mol Med Histol Histopathol…”
Section: The Markers Used To Identify Cardiac Tcs Can Be Challengedmentioning
confidence: 99%
“…Role of telocytes in the heart in health and diseases [Liskova et al, 2017] Arkh Patol c-kit Myocardial telocytes: a specific new cellular entity [Kostin, 2010] Telocytes form networks in normal cardiac tissues The failing human heart is characterized by decreased numbers of telocytes as result of apoptosis and altered extracellular matrix composition [Richter and Kostin, 2015] iPSC-derived human cardiac progenitor cells improve ventricular remodeling via angiogenesis and interstitial networking of infarcted myocardium [Ja et al, 2016] Cardiac telocytes as principal interstitial cells for myocardial reparation and regeneration after infarction -our hope [Varga et al, 2017a] Bratisl Lek Listy J Cell Mol Med Histol Histopathol…”
Section: The Markers Used To Identify Cardiac Tcs Can Be Challengedmentioning
confidence: 99%
“…Despite the fact that this method seems to be unrelated to TCs, it was observed that 4 weeks after transplantation endogenous and exogenous cardiac TCs appeared and intermingled in the infarction zone. What is the most important is the fact that recovery of their network in ischaemic area coincided with increased angiogenesis and improvement of myocardial strain (43,44).…”
Section: Current Achievements Of Tcs-related Experimental Therapiesmentioning
confidence: 99%
“…There are different types of stem cells such as embryonic stem cells, adult stem cells, and induced pluripotent stem cells for treatment of CVDs (Table 1). Previous studies have demonstrated therapeutic effects of ESCs differentiated into cardiomyocytes [17] and endothelial cells [18] for myocardial infarction, umbilical-cord-blood-derived MSCs for dilated cardiomyopathy [19], bone-marrow-derived-MSCs for cellular cardiomyoplasty [20], and iPSCs [21] and iPSCs-derived cardiovascular progenitor cells [22], endothelial progenitor cells (EPCs) [23], and cardiac stem cells [24] for myocardial infarction.…”
Section: Cardiovascular Diseases and Stem Cellsmentioning
confidence: 99%